Bosentan in heart transplantation candidates with severe pulmonary hypertension: efficacy, safety and outcome after transplantation. (2nd August 2012) - Perez‐Villa, Felix; Farrero, Marta; Cardona, Montse; Castel, Maria Angeles; Tatjer, Irene; Penela, Diego; Vallejos, Isabel
Abstract Background Increased pulmonary vascular resistance (PVR) is associated with increased right ventricular failure and mortality after heart transplantation. Methods In this prospective study, 22 patients considered high‐risk candidates for heart transplantation because of severe pulmonary hypertension (PVR = 6 ± 2 Wood units; transpulmonary gradient 22 ± 7 mmHg), received bosentan 125 mg bid. Right heart catheterization was repeated after four months (n = 22) and 12 months (n = 9). Eleven patients who declined participation in the study were considered as control group. Results After four months, PVR decreased by 38% in patients receiving bosentan (n = 22), while it increased by 25% in the control group (p = 0.001). Those patients who received bosentan for 12 months (n = 9), experienced a 60% reduction in PVR compared to baseline (p = 0.003). Only three patients (14%) had no hemodynamic improvement with bosentan. After bosentan therapy, 14 patients (64%) underwent heart transplantation. Patients with high PVR who received bosentan showed a trend toward better one‐yr survival after transplantation than patients with PVR ≤ 2.5 Wood units transplanted in the same period of time (93% vs. 83%). Conclusions In patients considered high‐risk candidates for heart transplantation because of high PVR, therapy with bosentan is associated with a significant reduction in PVR and a good outcome after transplantation.